Предмет договору про передачу ноу-хау як виду договору у сфері трансферу технологій - Розгон, О. В. (Право, 2019)
У цій статті аналізується категорія ноу-хау як форма комерційного трансферу та об’єкт інтелектуальної власності. Розглянуто варіанти співвідношення трансферу технологій і комерціалізації технологій. Виявлено проблеми ідентифікації предмета договору про передачу ноу-хау. Запропоновано визначення ноу-хау як предмета договору про передачу ноу-хау як виду договору у сфері трансферу технологій. // This article analyzes the category of know-how as a form of commercial transfer and intellectual property. Variants of the ratio of technology transfer and technology commercialization are considered. Problems of identification of the subject of the agreement on transfer of know-how are revealed. The definition of know-how as a subject of the agreement on the transfer of know-how as a type of agreement in the field of technology transfer is proposed.
Keywords: ноу-хау; трансфер технологій; комерціалізація технологій; договір про передачу ноу-хау; know-how; technology transfer; technology commercialization; know-how transfer agreement